2010
DOI: 10.1177/0886260510363425
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Women’s Response Effectiveness and a History of Sexual Victimization

Abstract: This study evaluated the effects of a sexual victimization history and the contextual features of sexual activity and alcohol use on the effectiveness of women's responses to 44 written vignettes describing diverse dating and social situations. One hundred and one undergraduate women reported their history of sexual victimization and provided written descriptions of how they would respond to each vignette. Experts in the sexual violence research area then evaluated the effectiveness of these responses in decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 36 publications
6
53
0
Order By: Relevance
“…When they occur in childhood and adolescence, these events are associated with a greater incidence of high-betrayal assaultive events in later life (Gobin and Freyd, 2009), suggesting a pre- or post-morbid deficit in correctly evaluating (i.e., learning) trustworthiness of conspecifics and social situations and/or adaptively responding to violations of trust. In support of this, prior studies have found that young adult women with prior exposure to interpersonal violence demonstrated higher thresholds for judging social situations as risky and reported less response effectiveness in risky social situations (Wilson et al, 1999; Gidycz et al, 2006; Yeater et al, 2010; Yeater and Viken, 2010; Yeater et al, 2011). It has also been found that adults who retrospectively reported high betrayal trauma demonstrated greater errors in detecting violations to rules involving social exchange and/or safety precaution (DePrince, 2005).…”
Section: Introductionmentioning
confidence: 64%
“…When they occur in childhood and adolescence, these events are associated with a greater incidence of high-betrayal assaultive events in later life (Gobin and Freyd, 2009), suggesting a pre- or post-morbid deficit in correctly evaluating (i.e., learning) trustworthiness of conspecifics and social situations and/or adaptively responding to violations of trust. In support of this, prior studies have found that young adult women with prior exposure to interpersonal violence demonstrated higher thresholds for judging social situations as risky and reported less response effectiveness in risky social situations (Wilson et al, 1999; Gidycz et al, 2006; Yeater et al, 2010; Yeater and Viken, 2010; Yeater et al, 2011). It has also been found that adults who retrospectively reported high betrayal trauma demonstrated greater errors in detecting violations to rules involving social exchange and/or safety precaution (DePrince, 2005).…”
Section: Introductionmentioning
confidence: 64%
“…Notably, for participants with a history of sexual victimization, the refusal responses were both lower in refusal intensity and increased in refusal intensity at a lesser rate, indicating two potential pathways through which behavioral response may operate to alter risk for sexual victimization. Another study using the same vignette series asked participants to describe in an open-ended fashion their own responses that were then rated by experts (Yeater, McFall, & Viken, 2011). Using hierarchical linear modeling, this study found that victimization history had a moderating effect on the relationship between sexual activity, alcohol, and the effectiveness of the behavioral responses such that, as the levels of sexual activity and/or alcohol consumption increased, response effectiveness decreased.…”
Section: Brtt As An Internal Mechanism Of Sexual Revictimizationmentioning
confidence: 98%
“…Stimuli. Fifty-five written vignettes developed using qualitative and quantitative data collected from college women about their social and dating experiences were used in the current study (Yeater, McFall, & Viken, 2011;Yeater et al, 2010;Yeater et al, 2006). These vignettes were written in the first person and describe representative problem situations that college women are likely to face when they date or interact with men.…”
Section: Scale Of Ethnic Experiences (See)mentioning
confidence: 99%